Pemurnian Asap Cair Terhadap Kinerja Reaktor Pirolisis Melalui Proses Filtrasi Zeolit Aktif - Yunia Ningrum, Shinta Silir ; Abrina Anggraini, Sinar Perbawani (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2018)
A lot of fresh food are easily damaged so they use chemical preservatives. Liquid smoke is a natural preservative because it is safe for health and the environment. The raw material used by agricultural waste, namely coconut shell. Liquid smoke that is quality and safe to consume must go through a purification process to eliminating the content of benzo(A)pyrene compounds because it is a carcinogenic compound that is very dangerous for human health if consumed. The purpose of this study was to determine the quality of liquid smoke through a purification process using active zeolite filtration to optimize the performance of pyrolysis reactors to producing liquid smoke. This research was carried out by pyrolysis, distillation and filtration at optimum operating conditions then analyzed using GC/MS and LC/MS. The results of this study are the amount of yield of liquid smoke from coconut shells without drying and drying is 36% and 28.8%. The remaining charcoal from coconut shells is 33% and 50%. The number of components lost from coconut shells was 31% and 21.2%. The performance of liquid smoke equipment from coconut shell is 4.37 g / (jam.m) and 5.59 g / (jam.m). The quality of liquid smoke produced for phenol from coconut shell is 3.04%. The quality of acidity is 7.3%. The pH value is 2.31. Liquid grade 1 smoke from coconut shell was not detected of benzo (A) pyrene after passing the zeolite filtration process. The values ??of phenol content, acidity, pH value and undetectable benzo(A)pyrene compound on liquid smoke are indicate that zeolite filtration is very optimal and produces liquid smoke with good quality.